Design formation of a transmedia project - A. М. Arakelyan; Yu. V. Vorontsova (Вестник университета)
The modern media sphere is changing under the influence of socio-cultural, technical, technological and media processes. The article studies such a phenomenon of the media sphere as transmedia, which is characterized by the nonlinearity and hybridity of audiovisual forms. It is a new key feature of the media sphere and makes significant changes to screen art. As a result of the research, foreign theory and practice of forming the design of transmedia projects have been studied. The possibilities of using foreign experience in Russian conditions have been determined. Recommendations given for conducting a transmedia project in various areas have been, including improving the transmedia narrative in its basic concept using a systematic approach. The developed recommendation and methodological base for the formation of the design of transmedia projects has been practice-oriented. This method is aimed at solving problems, at the practical implementation of this approach to the implementation of transmedia projects. The recommendations demonstrate the need for narrative knowledge within the framework of a transmedia narrative, allowing users to engage and be motivated by a transmedia narrative, rather than simply distributing content through media channels. The possibility of using classical elements of an integrated approach to the formation of the design of a transmedia narrative in the transmedia approach has been investigated.